A Risky Way of Doing Good – Combining Personality and Cognitive Variables in a New Hierarchical Model of Investment Risk-taking in Social Entrepreneurship. Issue 3 (3rd July 2022) - Chipeta, Eleanor Meda; Kruse, Philipp; Venter, Robert
ABSTRACT: Social entrepreneurship (SE) combines the aspirations to create financial and social values. However, an SE-career is also considered risky and susceptible to failure. Despite a growing body of research examining the motivation of social entrepreneurs, studies on antecedents of investment risk-taking in SE are rare. The current study aims at crafting and empirically testing a hierarchical model comprising personality and cognitive antecedents of SE investment risk-taking. Using structural equation modeling and a sample of 411 business students, we find several direct effects of cognitive and indirect effects of personality variables. SE-scholars and educators should pay attention to this complex interplay in future studies and SE-courses.